Responsible pet ownership perception in elementary schools after an educational program in Southern Brazil - Graziela Ribeiro da Cunha; Camila Marinelli Martins; Maysa Pellizzaro; Cristiane Conceição de Barros; Raquel Santos Pampuch; Antônio Felipe Paulino de Figueiredo Wouk; Fernando Ferreira; Rita Cássia Maria Garcia; Alexander Welker Biondo (Brazilian Journal of Veterinary Research and Animal Science, 2016)
The impact of responsible ownership programs with the goal of promoting public health remains to be fully established in Brazil. This study aimed to evaluate the responsible pet ownership perception of public elementary school students and teachers after a four-year outreach educational program in the city of Pinhais, Southern Brazil. Questionnaires were distributed for self-answer by fourth-grade students and teachers of all city public elementary schools. A total of 1,022/1,332 students (76.7%) referred participated in the program. No significant differences were observed between participating and non-participating groups regarding the concepts of responsible ownership (p = 0.88), zoonoses (p = 0.09) and animal welfare (p = 0.94). However, the frequency of correct answers on responsible ownership and zoonoses concepts was significantly higher (p < 0.01) among student groups who participated 1 or 2 times (779/830; 93.8% and 506/813; 62.2%, respectively) in relation to the groups that participated > 2 times (144/165; 87.3% and 64/151; 42.4%, respectively). It was also significantly higher (p < 0.01) between ≤ 10 years group (991/1058, 93.7%) compared to group >10 years (158/180; 87.8%) in the first concept. Although most teachers approved the continuing program (128/137; 93.4%), they reported low rates on training participation (41/137; 29.9%) and use of available teaching materials (78/137; 26.9%). The study has shown that perception of responsible pet ownership in outreach education programs may be more easily absorbed by children under ten years of age and up to two participations.